Defining the Hyksos: A Reevaluation of the Title hk3 h3swt and Its Implications for Hyksos Identity - Candelora, Danielle.
This paper considers the significance of the title hk3 h3swt during the Second Intermediate Period through a theoretical framework of identity negotiation and transience in contexts of cultural contact. By studying extant examples of this title throughout pharaonic history in context, the unique nature of the title during the period of interest becomes apparent. The use of this title by the Hyksos reflects their self conception and helps to elucidate the process of identity negotiation within the borderland of the Eastern Delta.   doi: http://dx.doi.org/10.5913/jarce.53.2017.a010